Análise da recuperação natural de cobertura vegetal diante da susceptibilidade à erosão hídrica em latossolo vermelho: estudo de caso da área do campus da UFSCar, Sorocaba-SP - Costa, Júlia Rodrigues Zanella da (Universidade Federal de São Carlos, 2022)
Address how the action of water erosive agents influence the dynamics of the structural components of a soil, allows us to understand not only the stability of a pedological profile, such as the ability of vegetation cover to recover. The objective of the research was to analyze the possibility of recovering vegetation cover through the influence of physical, chemical and biological hazards in Red Latosol susceptible to the action of rain. For this purpose, the initial and final characterization of the degradation value (Vdi) and physiognomy for two plots at the Federal University of São Carlos, Sorocaba-SP, by Resolution 01 of the CONAMA of January 31, 1994. The presence or absence of canopy, epiphytes, litter, herbaceous and human interference was also quantified at the end of the design, resulting in physiognomies and final degradation values ​​(Vdf). The occurrence recovery was obtained by comparison, where Vdf < Vdi = progression and Vdf > Vdi = regression. Variations in the physical parameters showed a relationship with the moisture retention and infiltration capacity, due to the arrangement of the particles solids and porosity. The chemical variations tell how the conduction of particles by runoff affected the availability and cycling of nutrients to the development of plant cover. On the other hand, variations in biological parameters effects of the presence of plant species with the solubilization of minerals, soil structuring and water infiltration and drainage capacity. Same verified, the reduction in the values ​​of degradation of the plots cannot be fully associated with the success of the natural recovery process, depending on also the existence of native or exotic species and the management and conservation for areas exposed to natural and anthropic degrading actions.
Analysis of the natural recovery of vegetation cover from the susceptibility to water erosion in an red latossolo: a case study of the UFSCar campus area, Sorocaba-SP
Keywords: Estabilidade; Erosão; Degradação; Stability; Erosion; Degradation; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL